Participation patterns at the 1998–2003 Southern Criminal Justice Association annual meetings - Doerner, William G. (American journal of criminal justice, 2004)
This paper examines the distance participants were willing to travel to attend the 1998–2003 Southern Criminal Justice Association annual meeting sites. The authors evaluate whether holding the conference at various locations throughout the region impacts individual participation, membership, and institutional representation. The findings reveal that conference sites that require greater travel have lower attendance and do not capture new members. However, the strength of offerings and tourist attractions can offset the negative impact of greater travel. The analysis also identifies a core group of members who show up at the meetings no matter where they are held. Finally, the conferences do not attract much local interest. Recommendations that would enhance attendance at regional meetings are advanced.